2018
DOI: 10.1103/physreva.97.022324
|View full text |Cite
|
Sign up to set email alerts
|

Passive quantum error correction of linear optics networks through error averaging

Abstract: We propose and investigate a method of error detection and noise correction for bosonic linear networks using a method of unitary averaging. The proposed error averaging does not rely on ancillary photons or control and feedforward correction circuits, remaining entirely passive in its operation. We construct a general mathematical framework for this technique and then give a series of proof of principle examples including numerical analysis. Two methods for the construction of averaging are then compared to d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 14 publications
(27 reference statements)
0
13
0
Order By: Relevance
“…Duality quantum algorithm was proposed in 2002 [ 71 ] for the first time, and it developed fast [ 72 , 73 , 74 , 75 ]. Because both the products of unitary operations and linear combinations of unitary (LCU) operations can be realized by duality quantum algorithm, it has a lot of applications to investigate novel quantum systems [ 16 , 17 , 18 , 19 , 20 , 21 , 76 , 77 , 78 , 79 , 80 ], e.g., systems of large-scale silicon quantum photonics, efficient quantum simulations of open quantum systems, quantum secure computing, passive quantum error correction, etc. Duality quantum algorithm has become one of the strongest tool in designing quantum algorithms [ 81 ].…”
Section: Duality Quantum Algorithmmentioning
confidence: 99%
“…Duality quantum algorithm was proposed in 2002 [ 71 ] for the first time, and it developed fast [ 72 , 73 , 74 , 75 ]. Because both the products of unitary operations and linear combinations of unitary (LCU) operations can be realized by duality quantum algorithm, it has a lot of applications to investigate novel quantum systems [ 16 , 17 , 18 , 19 , 20 , 21 , 76 , 77 , 78 , 79 , 80 ], e.g., systems of large-scale silicon quantum photonics, efficient quantum simulations of open quantum systems, quantum secure computing, passive quantum error correction, etc. Duality quantum algorithm has become one of the strongest tool in designing quantum algorithms [ 81 ].…”
Section: Duality Quantum Algorithmmentioning
confidence: 99%
“…For design space optimization and improving scalability, we propose integrating the dual-sequential-CMAC architecture with a dynamic approach, which involves generating the algorithm matrix values at runtime, storing only input vectors in memory. Therefore the total memory, M DG , using this method is significantly reduced, as shown in (23). The algorithm matrix U QFT , see (6), is generated as part of the architecture using dedicated hardware units as shown in Figure 4.…”
Section: Area Optimization Using Dynamic Generationmentioning
confidence: 99%
“…An experimental realization of a quantum computing silicon chip was fabricated in the work of Qiang et al In contrast to other realizations, this quantum chip does not use product of unitary operation architecture as proposed in the work of Benioff, it employed the linear combinations of unitary (LCU) operations architecture, proposed in the work of Gui‐Lu . The LCU has found extensive applications in quantum algorithms recently, as reviewed in the work of Shao et al, extending to quantum machine learning, secure multiparty computing, and passive error correction …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Marshman et al [19] have shown that, for boson-sampling, it is possible to detect the presence of random phase errors without leaving the paradigm and that the conditional state on detecting the error has a lower error than would otherwise be the case. This was done using a redundant encoding of the passive linear interferometer with a particular network chosen for encoding and decoding of input single photons.…”
Section: Introductionmentioning
confidence: 99%